Intraoperative Electrocochleographic Characteristics of Auditory Neuropathy Spectrum Disorder in Cochlear Implant Subjects - Riggs, William J.; Roche, Joseph P.; Giardina, Christopher K.; Harris, Michael S.; Bastian, Zachary J.; Fontenot, Tatyana E.; Buchman, Craig A.; Brown, Kevin D.; Adunka, Oliver F.; Fitzpatrick, Douglas C. (Frontiers in Neuroscience, 2017)
Auditory neuropathy spectrum disorder (ANSD) is characterized by an apparent discrepancy between the measures of cochlear and neural function when viewed by surface electrode auditory brainstem response (ABR) testing. Clinical indicators of ANSD are otoacoustic emissions and/or cochlear microphonic (CM) combined with a small or absent wave V brainstem potential. Many patients with ANSD have speech impairment severe enough that cochlear implantation (CI) is indicated. To better understand the cochleae that give rise to properties requiring implantation, we performed intraoperative round window electrocochleography (ECochG) to tone bursts in children (n=167) and adults (n=163) who were undergoing CI. Magnitudes of the responses to tones of different frequencies were summed to measure the “total response” (ECochG-TR), a metric often dominated by hair cell activity, and auditory nerve activity was estimated visually from the compound action potential (CAP) and auditory nerve neurophonic (ANN) as a ranked “Nerve Score”. Subjects with hearing loss due to ANSD (45 ears in children, 3 in adults) had higher values of ECochG-TR, and particularly at higher frequencies (>1000 Hz), than in adult and pediatric non-ANSD subjects also receiving CIs. However, nerve scores of the ANSD group were similar to the other cohorts, and were dominated by the ANN to low frequencies. To high frequencies, a common morphology of ANSD cases was a large CM and summating potential, and small or absent CAP. Common morphologies in other groups were either only a CM, or a combination of CM and CAP. These results indicate that responses to high frequencies, derived primarily from hair cells, are the main source of the CM used to evaluate ANSD in the clinical setting. However, the clinical tests do not capture the wide range of neural activity seen to low frequency sounds.